Teaching competencies and Their Relationship With Work Satisfaction of physical educators In Baghdad governorate - Abd, Fatima; Ibrahim, Alaa; Kazem, Wedad (Journal of Physical Education, 2019)
Teaching competencies and Their Relationship With Work Satisfaction of physical educators In Baghdad governorate   The study aimed to identify the degree of teaching competencies and job satisfaction of the teachers of physical education in the province of Baghdad, and then find the relationship between them.  Use the descriptive approach in the style of associative relationships, the research community represented by teachers of physical education in the departments of education Karh (first, second, third) in the province of Baghdad. (522) teachers and (324) school principals distributed in (324) medium within the administrative configurations of these directorates for the academic year (2016 - 2017).   The measure (teaching competencies) included (47) words distributed across seven areas. And the measure of (job satisfaction) included (15) words. After the completion of the pilot experiment, the main survey was conducted. The forms of job satisfaction were distributed to the teachers. The forms of the teaching competency level were distributed to their school principals because they were directly responsible for their evaluation according to the system adopted by the Ministry of Education. After the completion of this survey, the results were categorized and processed statistically by the statistical pouch. The study concluded: - The teachers of physical education in the schools of Baghdad governorate - Karh need to improve their teaching competencies in various fields that help them to develop their abilities and abilities in teaching. - The teachers of physical education in Baghdad governorate schools feel their lack of job satisfaction. - The weakness of teaching competencies negatively impacted on the feeling of job satisfaction among teachers of physical education in the schools of Baghdad governorate - Karh, because of the relationship of a direct link between them. So researchers recommend: - The need to pay attention to development courses that help teachers of physical education in the Mediterranean to improve their teaching competencies in the physical education lessons in their schools and not only the technical courses for participation in school sports activity. - It is necessary to establish a mechanism of cooperation between the general directorates of education and the faculties of physical education and sports sciences to use specialized academic expertise in administration, management, teaching methods and psychology in order to improve the teaching competencies because of its positive feedback on the development of job satisfaction.